"Time-building specific" seismic vulnerability assessment of a hospital RC building using field monitoring data. (1st April 2016) - Karapetrou, S.; Manakou, M.; Bindi, D.; Petrovic, B.; Pitilakis, K.
Highlights: Seismic vulnerability assessment of a hospital building using monitoring data. Methodology for assessing the fragility considering the real structural state. Comparison of the building-specific with generic fragility curves for RC buildings. Seismic vulnerability assessment of RC buildings considering aging effects. Abstract: In the context of seismic vulnerability assessment of reinforced concrete (RC) buildings, the use of field monitoring data constitutes a significant tool for the representation of the actual structural state, reducing uncertainties associated with the building configuration properties as well as many non-physical parameters (age, maintenance, etc.), enhancing thus the reliability in the risk assessment procedure. In this study, the seismic vulnerability of existing RC buildings is evaluated, combining through a comprehensive methodology, the numerical analysis and field monitoring data. The proposed methodology is highlighted through the derivation of "time-building specific" fragility curves for an eight-storey RC structure (hospital building), built almost five decades ago, that is composed by two adjacent units connected with a structural joint. The assessment of the dynamic characteristics is performed using ambient noise measurements recorded by a temporary seismic network which was deployed inside the hospital. The modal identification results are used to update and better constrain the initial finite element model of the building, which is based on the available design and construction documentation plans. Three-dimensional incremental dynamic analysis is performed to derive the fragility curves for the initial as built model ("building-specific") and for the real structures as they are nowadays ("time-building specific"). The initial "building specific" curves are evaluated through their comparison with conventional generic curves that are commonly used in risk assessment studies. Moreover, in order to enhance the reliability of the obtained results, the "time-building specific" fragility curves, are compared to time-dependent curves derived for the hospital units adopting an appropriate for the specific case study corrosion scenario. Results derived from both approaches indicate that the consideration of the actual state of structures may significantly alter their expected seismic performance leading to higher vulnerability values.